Overview of BDS III new signals. Issue 1 (4th March 2019) - Lu, Mingquan; Li, Wenyi; Yao, Zheng; Cui, Xiaowei
Abstract: With the completion of the experimental and regional phases, China's BeiDou Navigation Satellite System (BDS) is being speedily expanded to a global and multifunctional satellite navigation system, BDS III. Confronted with challenges such as limited frequency resources and diversified user requirements, new signals with novel modulation techniques are adopted in BDS III. In addition to the legacy B1I and B3I signals, new open service signals, B1C and B2a/B2b, as well as some new authorized service signals, will be broadcast by BDS III satellites. Among them, B1C and B2a are compatible and interoperable with GPS and Galileo. The modulation techniques and the detailed signal structures of B1C and B2a are introduced in this paper, along with analysis of the initial in‐orbit test results of the new signals.